Learning Motivation of Religious Program in Senior High School Students Viewed Residence and Its Implication in Guidance and Counseling - Rahma Wati Wae; Yasrial Chandra (Universitas PGRI SUMATERA BARAT, 2018)
ABSTRACT Learning motivation can be defined as internal and external encouragement in the students to make a change over their behavior. Someone’s learning motivation is affected by various factors which might come either from themselves or from outside. The factor is gender residence. The purpose of this research was to reveal of religious program insenior high school students learning motivation viewed from residence and its implication in guidance and counseling. This research method was ex post facto by using a factorial design 2 x 2. The population of this research was the students of religious program in senior high school that consist of 108 people. All of the population was taken as the sample. The instrument of the research was Likert scale model. The data obtained in this research was analyzed by using analysis of variant (ANOVA).The results of data analysis indicated that: learning motivation of the students who lived in the boarding school and those who did not live in the boarding school was in high category in which there was not significant difference between learning motivation of student who lived in the boarding school and those who did not live in the boarding school. Keyword : Learning Motivation, Residence ABSTRAKMotivasi belajar merupakan dorongan internal dan eksternal pada diri siswa yang sedang belajar untuk mengadakan perubahan tingkahlaku. Motivasi belajar siswa banyak dipengaruhi oleh berbagai faktor yang berasal dari dalam diri dan luar diri. Faktor yang mempengaruhi motivasi belajar diantaranya adalah tempat tinggal. Penelitian ini bertujuan untuk mendeskripsikan motivasi belajar siswa Madrasah Aliyah Keagamaan (MAK) ditinjau dari tempat tinggal serta implikasinya pada layanan bimbingan dan konseling. Metode penelitian yang digunakan adalah ex post facto dengan desain faktorial 2 x 2. Populasinya adalah siswa MAK sebanyak 108 orang dan dijadikan sampel penelitian. Instrumen yang digunakan adalah model skala Likert. Data dianalisis dengan menggunakan teknik analisis varian (ANAVA). Hasil analisis data menunjukkan bahwa: motivasi belajar siswa ditinjau dari tempat tinggal yaitu siswa yang tinggal di asrama dan yang tidak tinggal di asrama berada pada kategori tinggi, dan tidak terdapat perbedaan motivasi belajar antara siswa yang tinggal di asrama dan yang tidak tinggal di asrama. Kata Kunci : Motivasi Belajar, Tempat Tinggal